Estimating Network Effects and Compatibility in Mobile Telecommunications - Michał Grajek (European School of Management and Technology (ESMT), 2007)
I develop a structural demand model for mobile telephone service, which facilitates the identification of network effects and compatibility between networks. Network effects are measured by the dependence of consumer willingness to pay on the installed base of subscribers. Compatibility is measured by the relative extent of cross- and own-network effects. I then estimate the model using quarterly panel data from the Polish mobile telephone industry from 1996-2001 and find strong network effects and - despite full interconnection of the mobile telephone networks - low compatibility. I also show that ignoring network effects leads to an overestimation of elasticity of demand.
urn:nbn:de:101:1-201106143391
Keywords: C51; D12; L96; 650; Structural Econometric Model; Network Effects; Compatibility; Mobile Telecommunications